Suboptimal dietary knowledge predicts lower diet quality for cancer prevention among university students in Beirut - Jana Jabbour; Rodeina Dandache; Maryam Al Slaybe; Lama Haisam Mattar; Rana Rizk (PLoS ONE, 2025)
University students are at a pivotal stage of shaping cancer risk factors. Little is known about their dietary behavior in Lebanon, a country heavily burdened by cancer. This cross-sectional study assessed the dietary knowledge of and adherence to cancer prevention guidelines among university students in Beirut, Lebanon. We hypothesized that students would exhibit low knowledge, poor diet quality, and that knowledge predicted diet quality. Dietary knowledge was explored using a dedicated questionnaire, with scores above the 60th percentile considered as Knowledgeable (Kn+), and those below as less knowledgeable (Kn-). Dietary adherence to cancer prevention guidelines and the predictors of the Alternative Healthy Eating Index (AHEI)- a measure of diet quality calculated using the Modified Mediterranean Prime Screen, were also examined. The sample included 300 participants (55% females, mean age: 20 years). The mean knowledge score was 49.5%. Over 50% of students were aware of the association between red and processed meat, sodium, fruits and vegetables, obesity, and cancer. Kn+ group had a higher intake of vegetables and a lower intake of meats and sweetened beverages. Increased knowledge (B = 0.78, 95%CI: 0.18,1.37) and high physical activity (B = 4.62, 95%CI: 1.66,7.59) were associated with elevated AHEI scores. A significant positive interaction was observed between knowledge and enrollment in a health-related major. University students’ dietary knowledge of and adherence to cancer prevention guidelines are suboptimal. Although higher knowledge predicts high-quality diets, the association was weak. Further studies should investigate the food systems influencing university students’ dietary intake of university students in Lebanon and identify effective interventions to enhance health behavior.